Increased plasma genistein after bariatric surgery could promote remission of NAFLD in patients with obesity - Wang, Geng; Wang, Yu; Bai, Jie; Li, Gang; Liu, Yang; Deng, Shichang; Zhou, Rui; Tao, Kaixiong; Xia, Zefeng (Frontiers in Endocrinology, 2023)
Bariatric surgery is associated with a positive effect on the progress of non-alcoholic associated fatty liver disease (NAFLD). Although weight loss is the obvious mechanism, there are also weight-independent mechanisms. In this study, We collected blood samples from patients with obesity before and 3 months after surgery and performed LC-MS-based untargeted metabolomics test to detect potential systemic changes. Plasma genistein (GE) was identified to be elevated after surgery. Both clinical data and rodent models suggested that plasma GE is negatively related to the degree of NAFLD. We then fed diet-induced-obese (DIO) mice with GE and we found that there was significantly remission of NAFLD. Both in vivo and in vitro experiments showed that GE could restrict the inflammation state in the liver and thus relief NAFLD. Finally, we used co-housing experiments to alter the gut microbiota in mice and it was identified that SG mice had s special gut microbiota phenotype which could result in higher plasma GE levels. By feces transplantation experiment (FMT), we found that only feces from the SG mice (and not from other lean mice) could induce higher plasma GE level. Together our studies showed that SG but not calorie restriction could induce higher plasma GE levels by altering gut microbiota. This change could promote NAFLD remission. Our study provides new insights into to the systemic effects of bariatric surgery. Bariatric surgery could affect remote organs via altered metabolites from gut microbiota. Our study also identified that additional supplement of GE after surgery could be a therapy for NAFLD.